RESILIENT TRADITIONS OF ISLAMIC THOUGHT: Navigating Religion and Politics in Indonesia’s Emerging Future - Zamhasari, Zamhasari (Bajang Institute, 2025)
This paper examines how the tradition of Islamic thought in Indonesia demonstrates resilience and the capacity for transformation in the face of contemporary socio-political changes—from identity polarization and populism, to the challenges of digital governance and environmental sustainability. Using a qualitative-interpretive approach based on literature, this study maps the philosophical foundations of resilience in Indonesian Islamic thought (ijtihad, maslahah, maqāṣid al-sharī‘ah, musyawarah/ijmā‘, and wasatiyyah), examines the dynamics of mass organizations (NU, Muhammadiyah) and the Islamist movement, and formulates the future direction of democratic, inclusive, and socially just religion-state relations. The paper’s novel contribution is the proposal of a “philosophies of resilience” framework as a lens to bridge tradition and innovation, formulate a values-based policy research agenda, and integrate the discourse of green Islam and digital ethics into the study of Indonesian religion-politics.